Teaching, gender, sexuality: contributions to teacher education - Maria do Carmo Gonçalo Santos (Tópicos Educacionais)
Didactics, as a field of study and work dedicated to critical education, is a fertile territory for teacher education, committed to dealing with differences. Gender and sexuality are discursive social constructions. The research analyzes the contributions of Didactics, in Pedagogy Courses, to the treatment of gender and sexuality differences in pedagogical practice. UFPE's Pedagogy Courses subsidize the research. The results point to a work committed to overcoming instrumental didactics and situated in critical didactics. The teachers point out the importance of gender and sexuality and say of their presence in the curriculum. The paper situates the need for a gender and sexuality approach focusing on Intercultural Critical Didactics.